Development and validation of a chromatographic method for determining Clematichinenoside AR and related impurities - Zhou, Yang (BioMed Central, 2012)
BACKGROUND: Clematichinenoside AR is a promising lead compound for the treatment of rheumatoid arthritis. A systematic research for the related impurities in AR bulk samples is still lacking. For the safe use of this natural product in future clinical practice, the structure and content of each constituent, including the main ingredient as well as the impurities in AR bulk sample must be characterized in detail. RESULTS: A simple and stability indicating RP-HPLC method was developed and validated for determining the purity of clematichinenoside AR (AR), a natural product from the roots of Clematis manshurica Rupr. (Ranunculaceae) with the potential of treating rheumatoid arthritis. Five impurities were characterized, and impurity 2 (Clematomandshurica saponin F) is a new triterpenoid saponin isolated from this product. Optimum separation for clematichinenoside AR and five related impurities was carried out on an Agilent octadecylsilane bonded silica gel column (TC-C18, 4.6 mm ×150 mm, 5 μm) using a gradient HPLC method. The validation results showed good sensitivity, specificity, linearity(r(2)>0.9992) precision(RSD<1.63%), accuracy(recoveries in the range of 95.60%-104.76%) and robustness. Three AR bulk samples containing all the impurities were examined by two methods, and the stability of correction factors for the determination of related impurities was discussed. The proposed stability-indicating method was suitable for the quality control of this natural product. CONCLUSION: Five related impurities of clematichinenoside AR were characterized, including a new triterpenoid saponins firstly found in clematichinenoside AR bulk samples. In the simple chromatographic method for determining clematichinenoside AR and its related impurities in bulk samples, the correction factor was better for the quality control in the relative stable concentrations.